Pelatihan Kepemimpinan Bidang Ketrampilan Public Speaking dan Penyusunan Program Kerja Kebidelan Seminari Palembang T.A. 2017/2018 - Clara, Catharina; Inharjanto, Anselmus; Ratnaningsih, Paskalina Widiastuti; Leovani, Ega; Irzawati, Ira (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Student organization is part of the formation at St. Paul’s MinorSeminary in Palembang, South Sumatra. Seminary’s new studentorganization committee has been assigned with various tasks related tothe vision of 4Ss (i.e. Sanctitas or Sanctity, Sanitas or Health, Scientiaor Science, and Socialitas or Communal Life). The aim of thisleadership training of public speaking skills and work programmeplanning for internal student organization of St. Paul Minor Seminary,Palembang in academic year 2017/2018 is to increase leadershipability of Seminary students (or seminarians) especially in selfmanagementand as internal student organisation committee bothpublic speaking and work programme planning. The methods usedwere lecture and group practice. This activity was conducted in twodays. The first day activities were discussing basic leadershipmanagement and public speaking continued with group practice. Thesecond day activity was introduction to work program planningcontinued with real practice in groups. The analysis result ofquestionnaire reveals that the respondents’ opinions dealing withtraining activities in leadership, self-management, public speaking,and work programme planning demonstrate that the average score isin the agree and strongly agree scales. This fact indicates that theactivity is beneficial for the seminarians. It facilitates the seminariansto improve their abilities related to leadership, public speaking andwork programme planning.